The Effect of Brand Trust on Customer Loyalty (Case Study of MViCall Application Users in Jabodetabek) - Saskia Prameswari; Levyda Levyda (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The progression of technological sophistication in application development has resulted in tools designed to optimize user accessibility and requirement fulfillment. Video tone applications, functioning as ring tone substitutes, represent one category of mobile applications attracting substantial user interest, as demonstrated by the MViCall feature developed by PT. Indonesia Satu Tujuh, a content provider enterprise. Empirical observation reveals a systematic decline in active MViCall users throughout 2022, with figures decreasing from 6,791 active subscribers in January to 2,831 in September. This attrition has been identified as resulting from customer perceptions of involuntary subscription enrollment accompanied by unauthorized credit deductions. The objective of this investigation is to elucidate brand trust and customer loyalty constructs associated with MViCall in the Greater Jakarta region, and to determine the causal relationship between brand trust and loyalty. Data acquisition for this study was conducted through questionnaire administration to 97 respondents constituting MViCall application customers in Jabodetabek, with data processing executed using Excel and IBM SPSS Version 26. Methodological approaches employed encompassed quantitative descriptive analysis, hypothesis testing, simple linear regression analysis, and coefficient of determination assessment. Empirical results indicate that the brand trust variable exhibits a mean value of 3.84, corresponding to a high categorical classification, while the loyalty variable similarly demonstrates high categorization with a mean value of 3.81, with statistical analysis confirming a significant effect of brand trust on loyalty. The research concludes with the recommendation that PT. Indonesia Satu Tujuh (MViCall) implement measures to enhance brand trust.